El uso de dispositivos móviles y su incidencia en el rendimiento académico en los estudiantes del séptimo año paralelo “a” de la escuela de educación básica “Eco. Abdón Calderón Muñoz”, año 2024. - Gamarra Gamarra, Maholy Marianela (2025)
The digital age has profoundly transformed educational processes, providing new opportunities for learning through the use of mobile devices. The objective of this research is to analyze the relationship between the use of mobile devices and the academic performance of seventh-grade students at the "Eco. Abdón Calderón Muñoz" Elementary School. The methodology applied was quantitative and qualitative, using student surveys and teacher interviews as data collection tools. The questions focused on evaluating the daily use of mobile devices and the activities carried out. The results of the surveys and interviews showed that, while mobile devices can be a useful tool for accessing educational information, excessive or inappropriate use has negative effects, such as distraction and dependence. Other devices are used on educational platforms, to study, complete assignments, or improve their understanding of topics covered in class. It was concluded that moderate and targeted use of mobile devices can improve academic performance, but that teachers should also be trained to provide appropriate guidance in the digital educational environment.